PELAKSANAAN KEGIATAN EKSTRAKURIKULER DRUMBAND DI SMP NEGERI 15 PADANG - Heri Heri; Syeilendra Syeilendra; Irdhan Epria Darma Putra (FBS Universitas Negeri Padang, 2017)
AbstractThe aims of this study is to describe the implementation of the extracurricular Drumband in SMPN 15 Padang. The type of research used is qualitative research that emphasizes the qualitative descriptive approach. This means that research data in accordance with existing on the object under study, the activity drumband in SMPN 15 Padang. The research data was collected by observation, interview, and documentation through data collecting instrument in the form of stationery and photo media / video recording data. The findings of the study indicate that although drumband practice at SMPN 15 Padang is well managed, there is a problem in the student participation in this activity. At the beginning of recruitment participants, usually students who are interested to follow drumband quite a lot. But over time many do not continue keiikutsernya it. After being reviewed in the field, the problem of lack of competing activities, lack of coach condition, and equipment that is not well maintained is the problem point in the extracurricular activities of Drumband at SMPN 15 Padang.Keywords: Implementation, extracurricular activities, Drum Band